French Colonial Companies and Business Secrecy: The Case of French Equatorial Africa during the 1913 Rubber Crisis - (:unkn) unknown (My University, 2024)
Business secrecy was one of the main features of capitalism in the Second Industrial Revolution. At the time, accounting information was confidential, and its circulation was limited to the legal minimum. However, a study of the concessionary companies in French Equatorial Africa reveals the opposite: their accounting information was widely disclosed. We seek to understand the reasons for this apparent paradox by studying the discourse produced by the concessionary companies, focusing on the 1913 rubber crisis. This reflection on the unequal dissemination of financial data enables us to characterize the specific features of the colonial context and its differences with respect to metropolitan capitalism.
Keywords: African Research